Human Papillomavirus: Detection Method and Infection - Syafruddin Ilyas (Talenta Publisher, 2022)
The Human Papilloma Virus (HPV) is a small non-enveloped DNA virus, around 8000 bp in size and only humans become its host by infecting skin epithelial tissue, human oral mucosa and anogenital epithelium. Human Papillomavirus is often found in patients and is ranked as the second most malignant disease in women, belonging to the Alphapapillomavirus genus. HPV infection can be identified through the structure of the HPV virus itself and the particles contained therein which initiate the carcinogenic process of its host. The research methods used in this study are literature studies. The literature study method is a series of activities related to the method of collecting library data, reading, recording and managing research materials. The method often used to detect HPV is the polymerase chain reaction (PCR). The viral cell reproduction process is aided by activated proteins E1, E2, E4, E5, E6, and E7, which also delay apoptosis and alter the host cell cycle in various ways to cause cell alterations that result in cancer cells.